Pineal Region Glioblastoma, a Case Report and Literature Review - Stowe, Hayley Beacher; Miller, C. Ryan; Wu, Jing; Randazzo, Dina M.; Ju, Andrew Wenhua (Frontiers in Oncology, 2017)
Introduction: Pineal region glioblastoma multiforme (GBM) is a rare disease entity with a generally poor prognosis. We present a case of a patient with an unresectable pineal region GBM treated with chemoradiation with favorable outcome. Case Background: A 65-year-old patient who presented with visual symptoms was found to have a pineal region tumor on imaging. A stereotactic biopsy showed a WHO Grade IV GBM, MGMT promoter methylated, IDH1 and 2 wild type. He was treated with radiotherapy with concurrent temozolomide, followed by adjuvant temozolomide. Disease progression occurred at 58 weeks post-biopsy, which prompted the initiation of bevacizumab. The patient is alive and functioning well as of his last follow up, 166 weeks from the initial biopsy. Discussion: On our review of the literature, 24 cases of pineal region GBM have been reported. The median reported survival for these previously reported cases is six months (range 2-24). This patient has the longest overall survival reported to date for a patient with this diagnosis. This is the first patient in the literature with pineal region GBM who has been reported to have MGMT promoter methylation. Concluding Remarks: Although pineal region GBM is a rare disease entity with a generally poor prognosis, long-term survival is achievable for select patients. MGMT promoter methylation may potentially have prognostic value. Favorable control of recurrent disease with the use of bevacizumab is possible.